2021
DOI: 10.4081/ejh.2021.3298
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Creutzfeldt-Jakob disease: Real-Time Quaking Induced Conversion (RT-QuIC) assay represents a major diagnostic advance

Abstract: Sporadic Creutzfeldt-Jakob disease (sCJD) is a rare and fatal neurodegenerative disorder with an incidence of 1.5 to 2 cases per million population/year. The disease is caused by a proteinaceous infectious agent, named prion (or PrPSc), which arises from the conformational conversion of the cellular prion protein (PrPC). Once formed, PrPSc interacts with the normally folded PrPC coercing it to undergo similar structural rearrangement. The disease is highly heterogeneous from a clinical and neuropathological po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
(176 reference statements)
0
1
0
1
Order By: Relevance
“…No presente momento, várias intervenções terapêuticas potenciais já foram testadas, mas nenhum tratamento se provou eficaz. 25 Em contrapartida, os recentes avanços em relação à compreensão da patogênese da DCJ, aumentaram a expectativa pelo surgimento de intervenções terapêuticas eficazes. 26 Neste contexto, a abordagem com o uso do medicamento antipsicótico Clorpromazina vem sendo utilizada visando a eliminação de príons, com bons resultados em camundongos até o momento, mas ainda sem expectativa de ser testada em seres humanos.…”
Section: Relato De Casounclassified
“…No presente momento, várias intervenções terapêuticas potenciais já foram testadas, mas nenhum tratamento se provou eficaz. 25 Em contrapartida, os recentes avanços em relação à compreensão da patogênese da DCJ, aumentaram a expectativa pelo surgimento de intervenções terapêuticas eficazes. 26 Neste contexto, a abordagem com o uso do medicamento antipsicótico Clorpromazina vem sendo utilizada visando a eliminação de príons, com bons resultados em camundongos até o momento, mas ainda sem expectativa de ser testada em seres humanos.…”
Section: Relato De Casounclassified
“…It was first established in 2011 [ 14 ] in cerebrospinal fluid and based on earlier methods using cyclic amplification [ 15 ]. The method is also able to detected PrP Sc seeding activity in other tissues such as olfactory mucosa, skin, and retina [ 16 ]. The diagnostic accuracy of CSF RT-QuIC was evaluated in multiple studies that reported sensitivities between 77 and 97% and specificities of > 99% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%